MEMBANGKITKAN JIWA NASIONALISME GENERASI MUDA MELALUI NILAI-NILAI PERJUANGAN BANGSA - Djoko Sutanto; Samsi; Maria Sri Widyastuti; Pramudita Kusuma Putri (Surakarta Abdimas Journal, 2024)
Abstract The activity with the theme of awakening a sense of nationalism in the younger generation through socializing the values ​​of the nation's struggle was carried out in the form of a workshop intended for members of the youth organization "Sinoman Taruna Jati" in Sajen Village, Trucuk District, Klaten Regency. This activity aims to provide an understanding of nationalism and the values ​​of the nation's struggle for the younger generation. The method used in this activity is discussion. The stages of implementing this activity include observation, interviews, discussion and evaluation. The discussion material included global changes and their impacts, nationalism and the values ​​of the nation's struggle. The method of carrying out activities is through lectures, questions and answers, and discussions. This activity was attended by 60 members of "Sinoman Taruna Jati". Community leaders responded very well to this activity and acknowledged that this activity had an impact on increasing the sense of nationalism of the younger generation in the Sidorejo environment, Sajen Village, Trucuk District, Klaten Regency. It is the hope of community leaders that activities like this can continue to strengthen the sense of national unity and integrity. Keywords: Young Generation, Globalization, Nationalism, National Struggle Values